Meningkatkan Partisipasi Siswa dengan Pendekatan PJBL di SD Negeri 02 Jambak - Zurima, Destia (EduSpirit : Jurnal Pendidikan Kolaboratif, 2024)
This study aims to enhance student participation in learning about the qualities of the Prophet by applying the Project-Based Learning (PJBL) approach in grade IV at SD Negeri 02 Jambak. The study uses a Classroom Action Research (CAR) approach consisting of two cycles. The results show that the application of PJBL significantly improved student participation. In Cycle I, although there was improvement, some groups remained less active. In Cycle II, by introducing variations in presentation methods, such as drama and role play, student participation increased significantly. Students became more creative, confident, and able to relate the material to everyday life. This study concludes that PJBL is an effective approach to enhance student participation and understanding in learning the qualities of the Prophet.